Using the PerPot meta-model to compare the effectiveness of training methods in aerobic gymnastics - Torrents, C.; Balague, N. (Sportinformatik gestern, heute morgen. Festschrift zu Ehren von Prof. Jürgen Perl, 2010)
Aerobic gymnastics is based on the ability to perform continuous complex and high-intensity movement patterns coordinated with music. These movements come from traditional aerobic exercises and are combined with flexibility and strength movements. International rules define the exercises included in competition routines, with arm push-ups and jumps being the main elements. Few published studies have ana-lysed the muscular and metabolic demands of aerobic gymnastics (Löpez, Vernetta & De la Cruz, 1999; Torrents, Peralta, Marina, & Balague, 1999), the conclusion to date being that maximum and - mainly - explosive strength are the main conditional capacities.